Intraspecific Thievery in the Ant Ectatomma ruidum is Mediated by Food Availability. (22nd February 2013) - Guénard, Benoit; McGlynn, Terrence P.
Abstract Animals modify their foraging strategies in response to environmental changes that affect foraging performance. In some species, cleptobiosis represents an alternative strategy for resource access. The environmental factors that favor the incidence or prevalence of cleptobiosis, however, are poorly described. The cleptobiotic Neotropical ant Ectatomma ruidum is characterized by a high frequency of thievery behavior, a specific type of intraspecific cleptobiosis, in which specialized thief workers insinuate themselves into nests of neighboring colonies and intercept food items brought into these nests. Here, we evaluate how colonies adjust thievery behavior in response to food availability. We supplemented food availability and measured how the incidence and intensity of thievery responded to resource availability. We found that the incidence and intensity of thievery decline in response to supplemental food, suggesting that thievery behavior is a response to resource limitation at the population scale. This finding indicates that the phenomenon of intraspecific thievery, although a rare strategy in among colonies of social animals, is a viable alternative foraging tactic in the context of competition and food limitation.